Prospective study of efficacy and safety of non-ablative 1927 nm fractional thulium fiber laser in Asian skin photoaging - Li, Xianwen; Qin, Si; Shi, Siman; Feng, Yingjun; Li, Huarun; Feng, Yuqin; Li, Mujin; Wen, Ju (Frontiers in Surgery, 2023)
Background and Objective: Photoaging manifests as deeper wrinkles and larger pores. It has been tried to rejuvenate photoaging skin using a variety of lasers, including fractionated lasers, which are a popular photorejuvenation treatment. Recently, new laser and light-based treatment options have been used. one of these treatment modalities is the 1927 nm fractional thulium fiber laser (FTL), which is regarded as a new breakthrough for skin rejuvenation. Clinical data regarding the FTL for treating photoaging are limited despite its effectiveness and safety. This study is aim to evaluate FTL' clinical effectiveness and safety. Methods: Fitzpatrick skin types II–IV subjects with mild to moderate photoaging signs were enrolled in this prospective study. At intervals of one month, patients received three full face treatments. Wrinkles, spots, texture and pores were measured by VISIA system. Melanin index, erythema index (MI and EI), skin elasticity and hydration were measured with high frequency skin ultrasonography (Dermascan C USB) The epidermal thickness and dermal density on ultrasonography were compared between baseline and one month after all treatment sessions. The Global Score for Photoaging scale (GSP) was rated by two independent evaluators at the baseline and final follow-up visit. Secondary outcomes included patient-rated pain on a 10-point visual analog scale (VAS), as well as overall satisfaction. Following each treatment, adverse events were noted. Results: Totally 27 subjects (24 females and 3 males) with Fitzpatrick skin types II to IV and a mean age of 44.41 (range33–64) were enrolled. Results suggests that the epidermal thickness has significantly increased after treatment. Statistically significant improvements in melanin index, skin elasticity and wrinkles were noted. An analysis of 12 subjects’ reports (44%) suggested their skin felt brighter. No post-inflammatory hyperpigmentation changes or adverse events were observed. Patient satisfaction responses score was 2.04 ± 0.80, with 70% patients reporting “satisfied” or “extremely satisfied.” Conclusions: In this study, FTL were found to be safe and effective treatment options for treating photoaging.